Answer:
Part 1: AJ reflected over x-axis.
Part 2: [tex](0,-5)[/tex] and [tex](-1,-2)[/tex]
AJ plotted the graph using the function [tex]f(x)=(x+2)^{2}-1[/tex] . This resulted the graph to reflect over x-axis
Step-by-step explanation:
Part 1: AJ mistakenly plotted over x-axis, which means he reflected the graph over x-axis.The x-value remains the same. Only the y-values are transformed into its opposite sign.
Part 2:
Step 1: Plotting any two values for the function [tex]f(x)=-(x+2)^{2}-1[/tex]
Substituting x=0, we get,
[tex]\begin{aligned}y=f(0) &=-(0+2)^{2}-1 \\=&-(2)^{2}-1 \\=&-4-1=-5 \\& y=-5\end{aligned}[/tex]
Substituting x=-1, we get,
[tex]\begin{aligned}y=f(-1) &=-(-1+2)^{2}-1 \\=&-(1)^{2}-1 \\=&-1-1=-2 \\& y=-2\end{aligned}[/tex]
The two x-values for AJ’s function is [tex](0,-5)[/tex] and [tex](-1,-2)[/tex]
Step 2:
AJ plotted the graph using the function [tex]f(x)=(x+2)^{2}-1[/tex] . This resulted the graph to reflect over x-axis.